2021
DOI: 10.1515/biol-2021-0113
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of HLA-DRB1*11 and 1*12 alleles and risk factors in patients with breast cancer in Burkina Faso

Abstract: Several factors contribute to the development of breast cancer, including the immune system. This study is aimed to characterize the carriage of human leukocyte antigen (HLA)-DRB1*11 and 1*12 alleles in patients with breast cancer. This case-control study consisted of 96 histologically diagnosed breast cancer cases and 102 controls (cases without breast abnormalities). A multiplex polymerase chain reaction (PCR) was used to characterize the carriage of HLA-DRB1*11 and 1*12 alleles. The HLA-DRB1*11 allele was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…These results contrasted with observations in other diseases (e.g., breast cancer); HLA-DRB1*11 showed no association, while the deletion of this allele correlated with obesity. 19 Lymph nodes are crucial for several biological processes, including the development of metastasis and immune modulation. 26 Lymph-node invasion is a prognostic factor for many cancers such as CRC 27 and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results contrasted with observations in other diseases (e.g., breast cancer); HLA-DRB1*11 showed no association, while the deletion of this allele correlated with obesity. 19 Lymph nodes are crucial for several biological processes, including the development of metastasis and immune modulation. 26 Lymph-node invasion is a prognostic factor for many cancers such as CRC 27 and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CC is one of the most common malignancies worldwide. 1 Previous studies have highlighted the link between HLA class II gene polymorphisms and several diseases including type I diabetes 14 and aplastic anemia, 15 as well as several cancers including nasopharyngeal carcinoma, 16 glioblastoma, 17 CRC, 8,18 breast cancer, 19 and cervical cancer. 20 To the best of our knowledge, the association of DRB1 and DQB1 alleles/haplotypes with CC is not yet investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kagone et al 3 found a protective role of a variant of the DC‐SIGN promoter and of genetic resistance to HIV‐1 in serodiscordant couples in Burkina Faso; Compaoré et al (2016) 27 found that certain variants of APOBEC3G would protect against HIV‐1 infection 4,28,29 . Sorgho et al (2018−2019) showed that certain variants of KIR genes were associated with protection against HBV and HIV‐1 infection 4,29 and Zoure et al 30 found that HLA‐DRB1*11 allele deletion was associate with obesity/overweight, which is a risk for cancer development 30 in the same country.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average age of primiparity was very close to 24.04 years and the average number of children per woman was 2.39 children. These trends of late primiparity and low parity could partly explain the increase in breast cancer incidence in Burkina Faso ( 39 ).…”
Section: Discussionmentioning
confidence: 99%